Justified. Season 4 [videorecording (Blu-Ray)] - Olyphant, Timothy; Searcy, Nick; Carter, Joelle; Tazel, Erica; Goggins, Walton; Pitts, Jacob
In Season 4, Raylan will start to pick at the thread of a cold case over 30 years in the making, unraveling a riddle that echoes all the way back to his boyhood and his criminal father's bad dealings. Meanwhile Boyd Crowder finds his grip on Harlan loosening due to a Pentecostal preacher with a penchant for theatrics and a knack for manipulation to rival his own.